An Overview on Green Buildings (International Journal of Innovative Research in Computer Science & Technology, 2020)
Green construction has become one of the  recommended solutions for reducing the current building's  negative impacts on human health, society, industry  economy. However, in the future, there is an important use  of a comprehensive review of this massive amount of  material. In past decades, the amount of studies on green  building has skyrocketed. In the case of green architectural  development, this chapter provides a critical examination of  the existing corpus of knowledge. Thematic and quantitative  similarities in the research have been discovered. Green  structure's idea and scope, as well as the evaluation of  construction benefits over constructions and various ways  for producing green buildings, are all hot subjects. It was  determined that the majority of earlier studies on green  building had concentrated on the ecological impacts. Other  components of green construction sustainability are  sometimes overlooked, including good governance. The  influence of climatic factors on the usefulness of green  building rating methodologies, testing of real green  buildings, different population demands, and upgradeability  are all potential study subjects for the future.
Keywords: Assessment, Buildings; Energy Sustainability; Green building, Research review